Discordance of Low Density Lipoprotein and High Density Lipoprotein Cholesterol Particle vs Cholesterol Concentration for the Prediction of Cardiovascular Disease in Patients with Metabolic Syndrome and Diabetes Mellitus (from the Multi-Ethnic Study of Atherosclerosis [MESA]) - Tehrani, David M. (Am J Cardiol, 2016)
A stronger association for low and high density lipoprotein particle (LDL-P and HDL-P) versus cholesterol concentrations (LDL-C and HDL-C) in predicting coronary heart disease (CHD) has been noted. We evaluate the role of these factors and extent of particle-cholesterol discordance in those with diabetes (DM) and metabolic syndrome (MetS) for event prediction. In the Multi-Ethnic Study of Atherosclerosis, we examined discordance of LDL and HDL (defined as a subject’s difference between baseline particle and cholesterol percentiles), LDL-C, LDL-P, HDL-C, and HDL-P in relation to incident CHD and cardiovascular disease (CVD) events in subjects with DM, MetS (without DM), or neither condition using Cox regression. Among 6,417 subjects with 10-year follow-up, those with MetS (N=1596) and DM (N=838) had significantly greater LDL and HDL discordance compared to those without these conditions. In discordance models, only LDL discordance [per standard deviation (SD)] within the MetS group was positively associated with CHD events [adjusted hazard ratio (HR) =1.22, 95% confidence interval (CI):1.01–1.48, p<0.05]. In models with individual particle/cholesterol variables (per SD), within the DM group, HDL-P was inversely (HR=0.71, 95% CI: 0.52–0.96, p<0.05) and LDL-C positively (HR=1.47, 95% CI: 1.07–2.03, p<0.05) associated with CHD. In those with MetS, only LDL-P was positively associated with CHD (HR=1.34, 95% CI: 1.00–1.78, p<0.05). Similar findings were also seen for CVD. LDL discordance and higher LDL-P in MetS, and higher LDL-C and lower HDL-P in DM, predict CHD and CVD, supporting a potential role for examining lipoprotein particles and discordances in persons with MetS and DM.